OVARIAN CANCER INCIDENCE TREND IN THE NIŠAVA DISTRICT - Kocic, Biljana (Acta medicae Medianae, 2021)
Ovarian cancer represents the third most common gynecological cancer worldwide, and the most lethal one. The aim of the study was to assess ovarian cancer incidence trend in Nišava District in the period 1999-2017. Descriptive epidemiological method was applied. Data used for analyses were provided by the Cancer Register of the Institute of Public Health Niš and from the Serbian Cancer Registry. Incidence trends were based on crude and age-standardized incidence rates, calculated by the direct method of standardization per 100,000. Ovarian cancer represented 5.1% of all new registered malignant diseases in females with a total of 791 new cases. Ovarian cancer cases didn‘t registered before the age of 15. A statistically significant increasing trend with aging was registered. The average annual crude incidence rate was 22.0/100,000, while the average age-standardized incidence rate was 13.3/100,000. The highest age-standardized incidence rate was registered in 2016 (20.4), while the lowest rate was reported in 2002 (10.1). Ovarian cancer incidence trend, based on crude incidence rates, as well as on age-standardized incidence rates, increased. The highest age-adjusted incidence rate was in the municipality of Svrljig (18.4) and Gadžin Han (14.0) and the lowest registered in the municipality of Merošina (7.4) and Doljevac (9.0). Registration of unfavorable incidence trends of the disease indicate failure in primary and secondary prevention in the past. It is of vital importance to provide much intensive and comprehensive activities that may lead to the reduction of risk factors and to early detection of the disease.